Preparation and study of TiN nanostructured thin films by DC reactive magnetron sputtering with different mixing ratios of Ar:N2 - ضعون رهف; عدنان ميني; محمد بشير كرمان (Latakia University Journal -Basic Sciences Series, 2022)
Titanium nitride nanostructured thin films TiN were deposited at three different nitrogen ratio (10, 25, 50) % on unheated glass substrates using direct current DC reactive magnetron sputtering. These films were obtained with thicknesses (90,171,264) nm respectively. The structural, morphological, optical and electrical properties of these thin films were studied. X-ray diffraction (XRD) patterns showed an amorphous phase. Atomic Force Microscopy (AFM) measurements showed that the deposited thin films have a nanostructure, according to heights of their grains. An increase in roughness of the films was also observed with the increase in the nitrogen content. Spectroscopic analysis shows that the transmittance of films decrease with the increase of both nitrogen content and thickness of films. The values of the direct energy gap ranged between (3.57-3.33) eV. Photoluminescence emission of maximum intensity was obtained for the film deposited at 25% N2. Impedance measurements showed that films resistance did not change with the change of nitrogen content.